2021
DOI: 10.3390/su13031338
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Motivational Interviewing with Cognitive Behavioral Treatment on Behavior Changes in Heavy Drinkers

Abstract: This study aimed to investigate the efficacy of motivational interviewing (MI) with cognitive behavioral treatment (CBT) on behavioral changes of heavy drinkers. This study used embedded mixed methods that integrate sequential qualitative interviews with quantitative evaluation. Of a total of 47 participants, 24 belonged to an intervention group, which participated in the MI with CBT on behavioral changes once a week, 25–30 min on average, for 8 weeks. A total of 23 participants were assigned to a control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…An important finding from our NMA is that combined interventions provide enhanced effects in reducing AUDIT scores. MI in combination with CBT shows better outcomes than minimal interventions (such as a brief intervention alone), which is consistent with findings from the landmark combined pharmacotherapies and behavioral interventions for alcohol dependence (COMBINE) trial [59, 60], and has shown to produce more awareness in drinking behaviors [61]. Additionally, the combination has been shown to be effective in other substance abuse disorders, such as marijuana [62] and amphetamines [63].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…An important finding from our NMA is that combined interventions provide enhanced effects in reducing AUDIT scores. MI in combination with CBT shows better outcomes than minimal interventions (such as a brief intervention alone), which is consistent with findings from the landmark combined pharmacotherapies and behavioral interventions for alcohol dependence (COMBINE) trial [59, 60], and has shown to produce more awareness in drinking behaviors [61]. Additionally, the combination has been shown to be effective in other substance abuse disorders, such as marijuana [62] and amphetamines [63].…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, the combination has been shown to be effective in other substance abuse disorders, such as marijuana [62] and amphetamines [63]. One reason the blend of MI–CBT may be so beneficial is that a motivation for change is first established, which is directly followed by a personalized behavior action plan [61]. Nevertheless, CBT and more intensive interventions may require expertise or resources that may not be readily accessible in primary care environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies analysed, 2(12.5%) looked at the worth of MI combined with CBT along with 'change talk' and 'maintain talk' in their reactions among heavy drinkers' on behavioural changes 27,28 . After then, data was related to drinking consequences at 3 months.…”
Section: Resultsmentioning
confidence: 99%